2017
DOI: 10.3847/1538-4357/aa6c5b
|View full text |Cite
|
Sign up to set email alerts
|

The IRX–β Relation: Insights from Simulations

Abstract: We study the relationship between the UV continuum slope and infrared excess ( º L L IRX IR FUV ) predicted by performing dust radiative transfer on a suite of hydrodynamical simulations of galaxies. Our suite includes both isolated disk galaxies and mergers intended to be representative of galaxies at bothz 0 and~-z 2 3. Our lowredshift systems often populate a region around the locally calibrated Meurer et al. relation but move above the relation during merger-induced starbursts. Our high-redshift systems ar… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 96 publications
2
45
0
Order By: Relevance
“…An alternative scenario that does not involve starbursts or mergers is predicted by hydrodynamical simulations. These suggest that isolated normal main-sequence galaxies with log(L FIR /L e )<12 can populate the upper-left part of the IRX−βdiagram naturally due to their high gas fractions and high metal enrichment (e.g., Hopkins et al 2010;Safarzadeh et al 2017). The observed increase in gas fraction toward higher redshifts (Tacconi et al 2010;Genzel et al 2015) would make such a configuration likely for the most metal-rich galaxies in the early universe.…”
Section: Correlation Between the Location On The Irx−βdiagram And Phmentioning
confidence: 99%
“…An alternative scenario that does not involve starbursts or mergers is predicted by hydrodynamical simulations. These suggest that isolated normal main-sequence galaxies with log(L FIR /L e )<12 can populate the upper-left part of the IRX−βdiagram naturally due to their high gas fractions and high metal enrichment (e.g., Hopkins et al 2010;Safarzadeh et al 2017). The observed increase in gas fraction toward higher redshifts (Tacconi et al 2010;Genzel et al 2015) would make such a configuration likely for the most metal-rich galaxies in the early universe.…”
Section: Correlation Between the Location On The Irx−βdiagram And Phmentioning
confidence: 99%
“…Only if these deviations can be described as a function of other parameters can the IRX -β relation really be used to account for obscured SF. Safarzadeh, Hayward & Ferguson (2017) conclude that variations in the dust composition are the dominant source of variations in the IRX -β relation in their simulations. Kong et al (2004) suggested that the ratio of the present to past average SFR defines the deviation of galaxies away from the canonical Meurer et al IRX -β relation.…”
Section: Analytic Approximation For the Irx -β Relationmentioning
confidence: 99%
“…Multiple theoretical efforts have addressed the origin of observed variations in the IRX -β relation (e.g., Granato et al 2000;Ferrara et al 2016;Mancini et al 2016;Cullen et al 2017;Narayanan et al 2017;Safarzadeh, Hayward & Ferguson 2017). These works have highlighted stellar population age, variations in the dust attenuation curve, the temperature of the dust, and the geometry of the dust distribution as possible origins for observed deviations from the Meurer et al IRX -β relation.…”
Section: Introductionmentioning
confidence: 99%
“…Various theoretical efforts have attempted to explain the apparent deviations from the local IRX-β relation (Ferrara et al 2017;Safarzadeh et al 2017;Popping et al 2017;Narayanan et al 2018a). It was proposed that the most probable reason for the blue, dusty star-forming galaxies lying above the local relation, is the irregular relative covering of the dust and stars, where the least dust-attenuated regions produce blue UV colours, while the dusty parts give rise to the high values of the IRX.…”
Section: Introductionmentioning
confidence: 99%